PENENTUAN JUMLAH TENAGA KERJA OPTIMAL UNTUK MEMENUHI PERMINTAAN PRODUK PERCETAKAN DARI MESIN CETAK OFFSET: Studi Kasus: Percetakan Exodus House of Printing - Arvy Argadya Fortunata; Siti Mundari (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
Exodus House of Printing is a Home Industry printing which is located in Mojokerto. Home Industry is engaged in printing one of its products, namely invitations, calendars and brochures. Home Industry at this time must prioritize efficiency and effectiveness in carrying out production activities of a product. A company can be said to be effective when scheduling a product in the completion of a request from a consumer. One of the factors that influence the completion of a request is working time, workers/labor who take part in the completion of a production. The purpose of this study, among other things, is to find out the standard time for each worker and how much labor is optimal and how to plan costs in order to minimize expenses. By using several methods including stopwatch time, workload analysis, aggregate planning heuristics. After the method was applied, it was found that the research results showed that the process of making 1-unit product took 8.55 minutes with 6 workers for each operator with additional overtime and costs at least IDR 17,132,614